Mechanisms of oncolytic activity of Newcastle disease virus strain AF2240 in human renal carcinoma cell line - Ch'ng, Wei Choong (2014)
Newcastle disease virus (NDV) is an oncolytic virus that is known to selectively replicate in cancer cells compared to normal cells. It has been proposed that this preference is due to a defect in the cancer cells' interferon (IFN) responses. The exact mechanism underlying this process, however, remains unknown. In the present study, the antiviral response towards NDV infection by clear cell renal cell carcinoma (RCC) cells was examined. The most common first line treatment of RCC is using IFN. Unfortunately, most RCC cases are diagnosed at a late stage and often are resistant to IFN therapies. Alternative treatment approaches, including virotherapy, using oncolytic viruses, are currently being investigated. The present study used proteomic, molecular, immunological and biochemical techniques to investigate the mechanistic pathways that are involved in the response of RCC cells with defective or reconstituted wild type (wt) von Hippel-Lindau (VHL) gene activity to an oncolytic NDV infection. It was observed that NDV induced activation of NF-B in RCC cells by inducing phosphorylation of IB and its subsequent degradation. IB was phosphorylated as early as 1 hour post-infection and resulted in rapid NF-B nuclear translocation and activation. Importantly, p38 MAPK phosphorylation occurred upstream of the NF-B activation. These data provide evidence for the involvement of the p38 MAPK/NF-B/IB pathway in NDV infection and eventual apoptosis of RCC cells. Since the results indicated that there was a possible correlation between the pathway and IFN-β signaling, additional experiments were performed to further understand the IFN-β signalling, specifically STAT pathway, in NDV-infected RCC cells under various microenvironmental factors. The complexity of solid tumor microenvironments includes regions of hypoxia. In these regions, the transcription factor, hypoxia inducible factor (HIF), is active and regulates expression of many genes that contribute to aggressive malignancy, radioand chemo-resistance. To investigate the oncolytic efficacy of a highly virulent (velogenic) Newcastle disease virus (NDV) in the presence or absence of HIF-2α,renal cell carcinoma (RCC) cell lines with defective or reconstituted wild type (wt) von Hippel-Lindau (VHL) gene activity were used. The data showed that these RCC cells responded to NDV by producing only IFN-β, but not IFN-α and are associated with increased STAT1 phosphorylation. Restoration of wt VHL expression enhanced NDV-induced IFN-β production, leading to prolonged STAT1 phosphorylation and increased cell death. Hypoxia augmented NDV oncolytic activity regardless of the cells' HIF-2α levels. In summary, this study demonstrates IFN-β may play important role in NDV oncolysis through activation of p38 MAPK/NF-B/IB and STAT pathways in renal cell carcinoma. Altogether, these findings provide a better mechanistic understanding of NDV-mediated cell death and also highlight the potential of oncolytic local strain of NDV AF2240 as a potent therapeutic agent against normoxic and hypoxic cancer cells, especially renal cell carcinoma.